FROM IDEA TO ITS REALIZATION: NEW TRAINING CENTER IN THE INSTITUTE FOR EMERGENCY MEDICINE, BELGRADE - Andjelic, Sladjana Lj; Colakovic, Goran; Pavlovic, Aleksandar (Halo 194 Scientific Journal of Emergency Medicine, 2025)
At the end of 2015, at an unofficial meating Goran Čolaković, MD, director of the Institute for emergency medicine in Belgrade (IEM), Slađana Anđelić, MD, Phd, coordinator of the IEM education center and Aleksandar Pavlović, MD, PhD, the initiator and founder of the Center for simulation of the Faculty of medicine of Priština, based in Kosovska Mitrovica, the idea of forming a new Training center IEM was born. The training center is imposed as a result of the need for a modern approach in education in the field of various urgent clinical conditions. This vision requires a new spatial and tehnical structure equipped with modern phantom mannequins (trainers) and medical devices and equipment. According to the project financed by the European Union and the European Bank for Reconstruction and Development (EBRD), in July 2021, the reconstruction of the ZUM building with a training center of over 2,000 m2 began. With the tendency to sublimate all the necessary skills and knowledge in taking care of urgent clinical conditions in real conditions, the Center would have two simulation centers, five training rooms, two hooded rooms and a large amphitheater with a library.
Keywords: Training cenetr; Institute; emergency medicine